Sailing through a storm: The importance of dialogue in student partnerships - Macfarlane, Kirsty; Dennison, Jarah; Delly, Pam; Mitric, Damir (International Journal for Students as Partners, 2018)
The following is our collective attempt—staff- and student-centric, both in terms of outcomes and reporting—to unpack the complexities of our collaborative endeavour in 2017. We juxtapose our respective experiences of navigating the “normative hierarchical university paradigm” (Mercer-Mapstone et al., 2017, p. 18) to present a more collaborative and balanced discussion of our partnership. We reflect on our “way of doing things” (Healey, Flint, & Harrington, 2014, p. 12) so that the partnership process is more visible, particularly in relation to the challenges and negative outcomes. An ethos of reciprocity (Matthews, 2017) influenced our thinking and practice, and we were acutely aware of the complexities involved in real-life exchanges between staff and students. We discussed power openly throughout our collaboration, and here we speak about its function as equal co-authors of our empirical story. We are frank about the challenges that we faced and do not shy away from discussing failures, as well as lessons learned. We hope that this will help others to critically analyse and reflect on their own practice and, in the process, fully explore the transformative power of student partnerships for individuals and their institutions.